GAMBARAN POLA PEMBERIAN ASI DAN MP-ASI, STATUS GIZI DAN GANGGUAN SALURAN PENCERNAAN PADA BAYI USIA 0-6 BULAN DI DESA SUNGAI PAUH KECAMATAN LANGSA BARAT KOTA LANGSA TAHUN 2016 - Usi Purnama Tari; Ernawati Nasution; Evawany Y Aritonang (Gizi, Kesehatan Reproduksi dan Epidemiologi, 2017)
Breast milk is the best food for the babys first and that is natural,contains a variety of nutrients needed in the process of growth and development of infants. Bananas crew is a type of banana that is often given mothers to babies as breast milk in Aceh, but is still found giving the crew improrer bananas and given to infants under 6 months. Feeding too early can cause gastrointestinal disturbances such as diarrhea, vomiting, constipation. The purpose of research is to determine the pattern of breastfeeding, complementary feeding (bananas crew), nutritional status and the incidence of gastrointestinal disorders in infants aged 0 - 6 months in Sungai Pauh District of Kuala Langsa Kota Langsa. This study was descriptive cross-sectional design. The study sample consisted of 32 infants aged 0-6 months. Data about the patterns of breastfeeding and complementary feeding (banana crew) as well as gastrointestinal disorders was obtained through interviews with the babys mother. Weight (BB) was obtained by weighing the baby and body length (PB) by measuring the length of the body. The data has been analyzed descriptively. The results showed that most infants in Sungai Pauh crew fed baanas to the granting of the most widely performed include morning and afternoon (57,1%), frequency of administration as much as ≤ 3 times or 2 times a day (66,7%), means granting crew bananas crushed and screened (61,9%),  giving total quantity of 1 piece (71,4%) and the age of first granted since 0 months (42,9%). Breasfeeding patterns that most people do consist of granting non-scheduled time (77,8%), the frequency of ≥ 8 times (81,5%) and duration of ≥ 15 minutes (81,5%). Most babies have normal nutritional status based index of BB/U, PB/U, BB/PB. Digestive tract disorders occur most commonly in infants under 6 months of age with digestive disorders such as constipation (50%). It is advisable for the health center in order to improve the provision of counseling about bananas crew for babies over 6 months in order to decrease gastrointestinal tract disorders, in addition to the extension of the customary “peucicap” to be carried out as a gesture of course that exclusive breastfeeding is reached.   Keywords: babies 0-6 months, breastfeeding patterns, patterns of giving MP-ASI (bananas crew), nutritional status, digestive tract disorders